2017
DOI: 10.1007/s12630-017-1034-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of phenylephrine infusion versus bolus dosing for nausea and vomiting during Cesarean delivery in obese women

Abstract: Purpose Hypotension is common after spinal anesthesia for cesarean delivery. It is associated with nausea, vomiting and fetal acidosis. Previous research on phenylephrine excluded obese subjects. We compared the incidence of intraoperative nausea and vomiting (IONV) in obese patients who received a prophylactic phenylephrine infusion versus those who received phenylephrine boluses for the treatment of spinal-induced hypotension. Methods In this multi-centre, double-blinded randomized controlled trial, 160 ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Hypotension decreases cerebral blood flow and may lead to side effects such as nausea, vomiting, decreased consciousness, as well as respiratory and cardiac depression in the mother. Moreover, severe and sustained hypotension can reduce the uteroplacental blood flow and ultimately lead to fetal acidosis and depressed APGAR score ( 8 - 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypotension decreases cerebral blood flow and may lead to side effects such as nausea, vomiting, decreased consciousness, as well as respiratory and cardiac depression in the mother. Moreover, severe and sustained hypotension can reduce the uteroplacental blood flow and ultimately lead to fetal acidosis and depressed APGAR score ( 8 - 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, nausea and vomiting during surgery were less reported in the phenylephrine group than the control group, which is consistent with the results of other studies. For example, George et al (19) showed that intraoperative nausea and vomiting were significantly reduced in the prophylactic phenylephrine infusion group compared with the phenylephrine bolus (46% vs. 75%, respectively; relative risk = 0.61 (95% CI: 0.47 -0.80)), which was associated with the significantly reduced need for antiemetic drugs in this group. It was lower than the bolus group (26% vs. 42%; relative risk = 0.62 (95% CI 0.40 to 0.97) (19).…”
Section: Discussionmentioning
confidence: 90%
“…For example, George et al (19) showed that intraoperative nausea and vomiting were significantly reduced in the prophylactic phenylephrine infusion group compared with the phenylephrine bolus (46% vs. 75%, respectively; relative risk = 0.61 (95% CI: 0.47 -0.80)), which was associated with the significantly reduced need for antiemetic drugs in this group. It was lower than the bolus group (26% vs. 42%; relative risk = 0.62 (95% CI 0.40 to 0.97) (19). In a study by Atashkhoie et al (20) on 90 pregnant women under spinal anesthesia for elective cesarean delivery, nausea and vomiting in the phenylephrine and ephedrine infusion group (intervention group) was significantly lower than the placebo group.…”
Section: Discussionmentioning
confidence: 90%
“…1,2 We do agree that epidural anesthesia is indeed an option for cesarean delivery, though in our usual practice we generally prefer spinal anesthesia related to the overall better block quality and less need for supplementation or conversion to general anesthesia compared with epidural techniques. 3 We believe avoidance of general anesthesia is a primary goal in the obese population to avoid the potentially difficult airway.…”
Section: To the Editormentioning
confidence: 99%